Phase Compatible NiFe2O4 Coating Tunes Oxygen Redox in Li-Rich Layered Oxide - Peng, Jiming; Li, Yu; Chen, Zhiqiang; Liang, Gemeng; Hu, Sijiang; Zhou, Tengfei; Zheng, Fenghua; Pan, Qichang; Wang, Hongqiang; Li, Qingyu; Liu, Jianwen; Guo, Zaiping (ACS nano, 2021)
Li-rich layered oxides have attracted intense attention for lithium-ion batteries, as provide substantial capacity from transition metal cation redox simultaneous with reversible oxygen-anion redox. However, unregulated irreversible oxygen-anion redox leads to critical issues such as voltage fade and oxygen release. Here, we report a feasible NiFe2O4 (NFO) surface-coating strategy to turn the nonbonding coordination of surface oxygen into metal–oxygen decoordination. In particular, the surface simplex M–O (M = Ni, Co, Mn from MO6 octahedra) and N–O (N = Ni, Fe from NO6 octahedra) bonds are reconstructed in the form of M–O–N bonds. By applying both in operando and ex situ technologies, we found this heterostructural interface traps surface lattice oxygen, as well as restrains cation migration in Li-rich layered oxide during electrochemical cycling. Therefore, surface lattice oxygen behavior is significantly sustained. More interestingly, we directly observe the surface oxygen redox decouple with cation migration. In addition, the NFO-coating blocks HF produced from electrolyte decomposition, resulting in reducing the dissolution of Mn. With this strategy, higher cycle stability (91.8% at 1 C after 200 cycles) and higher rate capability (109.4 mA g–1 at 1 C) were achieved in this work, compared with pristine Li-rich layered oxide. Our work offers potential for designing electrode materials utilizing oxygen redox chemistry.